Debtors’ Protection on Bankruptcy and Postponement of Debt Payment Obligations: A Case Study in Indonesian Financing Sector - Sinaga, Henry Dianto P.; Emirzon, Joni (Scientia Business Law Review (SBLR), 2022)
Lawsuits of Bankruptcy and Postponement of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang or PKPU) are still easy weapons for financial institutions against debtors who are in arrears in paying their debts. In fact, a settlement can be made that should not impose further losses on the debtor, who has to sign a contract that benefits the creditor. Based on normative juridical studies, two conclusions are produced. First, the Bankruptcy and PKPU Law, Consumer Protection Law, Otoritas Jasa Keuangan (OJK) Law, P2SK Law, and POJK-7/POJK.05/2022 have not been able to protect debtors in the financing sector in the event of a bankruptcy and PKPU lawsuit. Second, ideally, consumer protection in the event of bankruptcy and PKPU in the financing sector in Indonesia is carried out by making regulations that enable consumers to report injustices they receive to independent consumer protection institutions and commercial courts and dispute resolution institutions between consumers as debtors and creditors. It must implement electronic options to provide certainty of justice and public benefits to the parties, especially consumers. It is recommended that in the future, there be recommendations from independent consumer protection institutions regarding standard contracts for financial institutions as well as commercial courts and online dispute resolution institutions.